2021
DOI: 10.18178/ijiet.2021.11.12.1570
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Online Learning Self-efficacy and Self-regulated Learning during the COVID-19 Pandemic

Abstract: The teaching and learning process has shifted online since the outbreak of COVID-19 in Indonesia. Students have had to adapt to the new situation. Thus, it is necessary to explore their self-efficacy and self-regulated learning. The objective of this paper is twofold: 1) to describe the profiles of students’ online learning self-efficacy and students’ online self-regulated learning; and 2) to investigate the relationship between self-efficacy and self-regulated learning in online learning among university stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…In addition, a study conducted among users of massive open online courses (MOOCs) found a positive correlation was found between self-efficacy and the use of self-regulated learning strategies, as well as differences in the use of self-regulated learning strategies between learners who had high self-efficacy and those who had low self-efficacy ( Lee et al, 2020 ). The same results are found in Ulfatun et al (2021) study with virtual learners in Indonesia.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, a study conducted among users of massive open online courses (MOOCs) found a positive correlation was found between self-efficacy and the use of self-regulated learning strategies, as well as differences in the use of self-regulated learning strategies between learners who had high self-efficacy and those who had low self-efficacy ( Lee et al, 2020 ). The same results are found in Ulfatun et al (2021) study with virtual learners in Indonesia.…”
Section: Discussionsupporting
confidence: 84%
“…Tang and Tseng (2013) stated online distance students who had a high level of selfefficacy displayed superior information searching and information manipulation skills. Whereas, Ulfatun et al (2021) revealed a strong positive correlation between students' online self-efficacy and online self-regulated learning. The two studies mentioned above further supported Kurbanoglu's (2003) conclusion that students are more inclined to engage in information problem-solving activities and are more likely to become self-regulated students when they feel competent and confident about their information literacy skills.…”
Section: Self-efficacymentioning
confidence: 88%
“…It was pointed by [29] that universities should motivate learners to use prior knowledge and skills to help them attain self-efficacy during ERT. In the study of [18], high online learning self-efficacy was found to be positively linked to online self-regulation which is likewise correlated with academic success.…”
Section: B Online Learning Self-efficacymentioning
confidence: 93%
“…This may be explained by the novelty of the online experience for students, as well as the abruptness of their transition to the virtual learning environment. The pandemic has been reported to increase anxiety and stress among learners, which negatively affect their satisfaction in an online course [18]. Among the independent variables, LCI had the strongest influence on SS (β = 0.469, p < 0.01).…”
Section: Regression Analysismentioning
confidence: 97%